Statistical Analysis and Modeling of Weight Loss in a Controlled Exercise Program - Abhijit Chitre , Archana Ratnaparkhi , Prathmesh Moralwar , Yash Dahale , Namrata Khade (South Eastern European Journal of Public Health, 2025)
This paper will examine a controlled 6- month exercise program to measure weight loss among the individuals. For this, we carry out the paired t-test to examine whether weight has actually decreased for the individuals in the last stage after the intervention. In the preliminary stages, our results indicate significant weight loss, showing how regular activity can work positively. Also, we take the comparison of the trends with respect to weight loss for the purpose of exercising in terms of duration. We use regression models to predict weight loss in terms of exercise duration and type. Further, we apply PCA to reduce the dimensionality of the set of fitness metrics, so we can focus on important factors, such as frequency of exercise and dietary habits, which affect the weight-loss outcomes most significantly. This broad investigation not only places great emphasis on exercise as a critical component in controlling weight but also provides a sturdy statistical foundation for further exploration of health and fitness programs.